2018
DOI: 10.1016/j.gore.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Linear accelerator-based radiosurgery and hypofractionated stereotactic radiotherapy for brain metastasis secondary to gynecologic malignancies: A single institution series examining outcomes of a rare entity

Abstract: ObjectiveThe use of SRS and fSRT to determine overall survival, tumor control, and local-disease free progression in patient diagnosed with gynecologic brain metastasis.MethodsIn this retrospective review, 11 patients aged 50 to 85 (median age of 71) were treated with linear accelerator-based SRS and hypofractionated SRT for brain metastasis secondary to gynecologic malignancies. In total, 16 tumors were treated from 2007 to 2017. Patients were treated to a median dose of 24 Gy (range 15 to 30 Gy) in 3 Fx (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our methods for brain SRS/SRT have been previously described, and are as follows. 14 Before treatment, a contrast-enhanced (i.e. gadolinium) T1-weighted neuronavigation magnetic resonance imaging (MRI) was performed with a resolution of 0.5 mm by 0.5 mm and a slice thickness of 1 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our methods for brain SRS/SRT have been previously described, and are as follows. 14 Before treatment, a contrast-enhanced (i.e. gadolinium) T1-weighted neuronavigation magnetic resonance imaging (MRI) was performed with a resolution of 0.5 mm by 0.5 mm and a slice thickness of 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…After CT image acquisition, the images were co-registered to the MRI data set in the Brainlab iPlan image software. 14 The treating radiation oncologist then contoured the gross target volume (GTV), which was expanded by a margin of 2 mm to generate the planning target volume (PTV). A treatment plan using 4 to 10 non-coplanar conformal arcs was generated using pencil beam algorithm in Brainlab iPlan Dose software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that only case reports, case series, and retrospective database studies provided information on number of patients, incidence rates, clinicopathological features, symptoms, and types of treatments. After screening the titles and abstracts, 83 full texts on BMs from CC and 78 full texts on BM from EC were selected and summarized (Table 1 and Table S1 [9,, Table 2 and Table S2 [6,9,20,28,31,37,40,41,46,49,53,55,59,62,63,[66][67][68][69][70][71][72][73][74][75][77][78][79]81,82,84,). Several case reports about the FIGO stage were lacking, and only histologic information was described.…”
Section: Resultsmentioning
confidence: 99%
“…The survival of BMs from EC is very poor, and depends on the status of the primary lesion, the presence of extracranial metastases, and the volume, number, and site of metastases in the brain parenchyma. The survival time after diagnosis of BMs from EC was available for 946 patients in the literature and ranged from 0.1 to 171 months (median: 7.5 months) [ 6 , 9 , 28 , 31 , 37 , 40 , 41 , 46 , 49 , 53 , 55 , 59 , 62 , 63 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 77 , 78 , 79 , 81 , 82 , 84 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ...…”
Section: Endometrial Cancermentioning
confidence: 99%